HUBUNGAN WORK ENGAGEMENT DENGAN TURNOVER INTENTION PADA KARYAWAN DI KSPPS TUNAS ARTHA MANDIRI KABUPATEN NGANJUK: Hubungan Work Engagement Dengan Turnover Intention Pada Karyawan Di Kspps Tunas Artha Mandiri Kabupaten Nganjuk - Mentari Marwa; Nila Ainu Ningrum; Muhammad Atha Naufal (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2022)
The occurrence of turnover begins with the intention of employees to resign from the company or in the world of industrial psychology it is called turnover intention. One of the strongest factors that can influence turnover intention in employees is work engagement, where when work engagement is low, the level of employee turnover intention increases. This study uses a quantitative research method with a sample of 30 respondents. The criteria are: gender, age, length of service. Data collection was carried out by interview, observation and Likert scale questionnaire with a reliability value of 0.911 and for turnover intention with a reliability value of 0.980 in the form of a google form. While data analysis uses a non-parametric correlation test tested with the Spearman's rho test. This test is assisted by the help of SPSS 30. The results of the study are a moderate level of work engagement of 24 respondents (80.0%), followed by a low level of 4 respondents (13.3%) and a high level of 2 respondents (6.7%). The turnover intention level was also dominated by the medium category, with the same number of respondents (24 people, 80.0%), followed by the high level (4 respondents, 13.3%), and the low level (2 respondents, 6.7%). Hypothesis testing of the relationship between work engagement and turnover intention revealed a significant negative correlation, with a correlation coefficient of 0.397 and a significance value of 0.030 (p<0.05). This indicates that the higher an employee's work engagement, the lower their tendency to have turnover intention, and vice versa. The significance of this relationship indicates a low strength.